Hubungan antara Dukungan Keluarga dengan Kepatuhan Konsumsi Tablet Fe pada Ibu Hamil di Wilayah Kerja Puskesmas Nanggalo Kecamatan Nanggalo - Esthika Ariany Maisa; Nelwati; Meri Neherta (NERS Jurnal Keperawatan)
The low adherence of pregnant women in consuming Fe tablets is regarded to be the main cause of the ineffectiveness of the Fe supplementation program held by the government to overcome anemia issues on pregnancy. One of the factors that influence the adherence of pregnant women is family support. This research was aimed at finding out the relationship between family support and the adherence in consuming Fe tablets among pregnant women in Puskesmas Nanggalo Kecamatan Nanggalo, Padang, West Sumatra in 2010. This research was designed in a correlation study with a cross-sectional approach and 32 respondents. Respondents were those who had got Fe tablets in their last visit from Puskesmas and also had a health history with anemia in pregnancy. The data was collected by using a questionnaire. Univariate and bivariate analyses were done to variable family support as well as the adherence of pregnant women. Bivariate analysis was done by cross-tabulation with a Chi-Square test. The result of the research showed that 54.9% of respondents got low family support and 71.9% of respondents had low adherence in consuming Fe tablets. From the statistics experiment, it can be concluded that there is a relationship between family support and women's adherence in consuming Fe tablets (p < 0.05). Therefore, it is suggested that nurses or other health workers in order to start asking and taking the family members, especially for husbands, to join treatment toward pregnant women with anemia.